Message from Editorial Board - Dhungana, Bharat Ram (Journal of Business and Management, 2025)
We are pleased to present the ninth volume (Issue 1) of the Journal of Business and Management (JBM). It is a B category academic journal as per UGC Nepal classification, published by the School of Business, Pokhara University. The Journal publishes research articles in management, economics, and related fields. The main objective of JBM is to provide a platform for disseminating knowledge that contributes to improving management practices in developing nations. It also provides a scholarly publication outlet for scholars. It promotes research in alternative paradigms for business management and economics. JBM enhances cooperation and communication among academics. We also seek to offer new perspectives on business management in line with our underlying commitment to a more ethical and sustained business culture. JBM envisions creating a new forum for the scholarly community by focusing on management issues in developing countries. We received 26 research papers and accepted only 9 research papers (34.62%) for publication after a blind peer review of each research paper by two peer reviewers. We also checked the similarity index and use of AI in the submitted research papers. As per the plagiarism policy of the Journal, we reject the AI used and 15% above similarity index research papers. In this issue, 18 authors contributed the papers as a collaborative and single authorship. The authors were from Pokhara University, Tribhuvan University, Kathmandu University, Far Western University and Indian universities including Sanskriti University, University of Allahabad, and Indira Gandhi National Tribal University. The Editorial Board would like to thank the authors and researchers who contributed to the ninth volume (Issue 1) of JBM. Also, we express our sincere gratitude to the advisory board of the JBM, peer reviewers, the Office of the Dean -Faculty of Management Studies and the School of Business, Pokhara University, Pokhara University Research Center, Pokhara University Central Library, NEPJOL, and all supporting hands for their valuable support in the process of publication. We anticipate critical feedback and constructive suggestions for improving the JBM in the upcoming issues. Thank you for considering JBM- The Journal of Business and Management as a publication outlet. The Editorial Board welcomes original research-based articles and expects your contribution, suggestion, and support for the upcoming issue. Associate Professor Bharat Ram Dhungana, Ph.D. Editor-in-Chief, The Journal of Business and Management School of Business, Pokhara University, Pokhara, Nepal June 30, 2025